Influence of common non-synonymous Toll-like receptor 4 polymorphisms on bronchopulmonary dysplasia and prematurity in human infants. - Pascal M Lavoie; Mihoko Ladd; Aaron F Hirschfeld; Johanna Huusko; Mari Mahlman; David P Speert; Mikko Hallman; Thierry Lacaze-Masmonteil; Stuart E Turvey (PLoS ONE)
Bronchopulmonary dysplasia (BPD) is a common chronic lung disease and major risk factor for severe respiratory syncytial virus (RSV) infection among preterm infants. The Toll-like receptor 4 (TLR4) is involved in oxidative injury responses in the lungs. Two non-synonymous single nucleotide polymorphisms in the TLR4 gene have been associated with RSV infection in children. However, it is unclear to what extent this association is confounded by BPD or prematurity. In this study, we analyzed two population-based cohorts of preterm infants at risk for BPD as well as ethnicity-matched infants born at term, to test whether the TLR4 polymorphisms Asp299Gly (rs4986790) and Thr399Ile (rs4986791) are independently associated with BPD or premature birth. In a Canadian cohort (n = 269) composed of a majority of Caucasian preterm infants (BPD incidence of 38%), the TLR4-299 heterozygous genotype was significantly under-represented in infants without BPD (1.6% of infants versus 12% in infants with severe BPD) after adjusting for twins, ethnicity, gestational age, birth weight and gender (p = 0.014). This association was not replicated in a Finnish cohort (n = 434) of premature singletons or first-born siblings of Caucasian descent, although the incidence of BPD was substantially lower in this latter population (15%). We did not detect a significant association (>2-fold) between TLR4 genotypes and prematurity (p>0.05). We conclude that these TLR4 genotypes may have, at best, a modest influence on BPD severity in some populations of high-risk preterm infants. Further studies are warranted to clarify how clinical heterogeneity may impact genetic susceptibility to BPD.